Efektivitas Acceptance and Commitment Therapy pada Orang Dewasa yang Mengalami Kecemasan dan Depresi: Studi Literatur - Benedicta Audrey Putri Trisnadewi; Puspita Puji Rahayu; Menik Tetha Agustina; Shofwatun Amaliyah; Ervina Kumalasari (Journal on Education, 2024)
This study aims to determine the effectiveness of Acceptance and Commitment Therapy (ACT) on adults who experience anxiety and depression in Indonesia. The method used in this research is a literature study. The inclusion criteria of this literature study were that the subjects were adults aged at least 18 years, used Acceptance and Commitment Therapy (ACT) as the intervention, was conducted in the Indonesian population, aimed to reduce the level and/or symptoms of anxiety or depression, written in Indonesian and English, and could be accessed in full-text. Articles were obtained through Google Scholar. There were 5 research articles included with a total of 73 participants. The results of the literature review found that ACT is effective in reducing levels and/or symptoms of anxiety and depression. Future researchers can include more research articles in the literature review or meta-analysis that reveals the effectiveness of ACT in adults with anxiety and depression in Indonesia.